2004
DOI: 10.1093/carcin/bgh211
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ICAM-1 gene expression, monocyte adhesion and cancer cell invasion by targeting IKK complex: molecular and functional study of novel  -methylene- -butyrolactone derivatives

Abstract: The transcription factor nuclear factor-kappaB (NF-kappaB) is a regulator related to cellular inflammation, immune responses and carcinogenesis. Therefore, components of the NF-kappaB-activating singnaling pathways are frequent targets for the anti-inflammatory and anticancer agents. In this study, CYL-19 s and CYL-26z, two synthetic alpha-methylene-gamma-butyrolactone derivatives, were shown to inhibit the tumor necrosis factor-alpha (TNF-alpha)-induced intercellular adhesion molecule-1 (ICAM-1) expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 44 publications
1
87
1
Order By: Relevance
“…The introduction of exogenous PGE 2 reversed the inhibitory effect of NS-398. Similar positive correlation between PGs productions and tumor invasiveness was observed in the lung cells (32). Cell line transfected with COX-2 (AGS/ COX-2) also exhibited high invasiveness and angiogenesis.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The introduction of exogenous PGE 2 reversed the inhibitory effect of NS-398. Similar positive correlation between PGs productions and tumor invasiveness was observed in the lung cells (32). Cell line transfected with COX-2 (AGS/ COX-2) also exhibited high invasiveness and angiogenesis.…”
Section: Discussionsupporting
confidence: 72%
“…COX-2 may play a role as survival factor in protecting cells from apoptosis (30). Furthermore, functions like the encouragement of cell proliferation (31), the induction of tumor cell invasion (32,33), the stimulation of angiogenesis (11), and the inhibition of immunosurveillance (34) have also been described. SC-236, a selective COX-2 inhibitor, was effective in reducing angiogenesis driven by the basic fibroblast growth factor in a Matrigel model (35).…”
Section: Discussionmentioning
confidence: 99%
“…35 VEGF has been reported to induce the proliferation of endothelial cells and increased vascular permeability, 10 whereas ICAM-1 is known to have an important role in lymphatic and vascular invasion, and subsequent adhesion to other tissues. 36 It has been reported that the expression of VEGF and/or ICAM-1 is correlated to the malignancy, or metastatic potential of tumors including osteosarcoma. 37,38 In our study, the mRNA levels of VEGF and ICAM-1 were significantly decreased by transfection of NF-kB decoy ODN, indicating that the metastatic potential of LM8 cells was decreased by the transfection of NF-kB decoy ODN.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM molecules may target and block tumor progression by stimulation of an immune response such as leukocyte activation (15,16). Conversely, other investigations have shown that ICAM molecules are involved in cancer malignancy because their increased expressions are associated with a poor diagnosis, lower survival rates and metastasis in some cancers including melanoma, breast cancer and leukemia (17)(18)(19)(20)(21)(22)(23)(24). We have also reported that an increase of ICAM-3 expression in several cancer cells and specimens of cervical cancer patients induced enhanced radio-resistance by the activation of focal adhesion kinase (FAK) (25) and promoted cancer cell proliferation by the activation of Akt and p44/42 MAPK (26).…”
Section: Introductionmentioning
confidence: 99%